Evaluasi Tingkat Kerusakan Jalan dengan Metode PKRMS (Provincial Kabupaten Road Managemen System) (Studi Kasus: Kabupaten Bengkulu Tengah) - Edo Jaya Saputra; Rezi Munizar (Journal of Science, Technology, and Innovation, 2026)
Road deterioration is a major transportation infrastructure issue influenced by various factors, including environmental conditions, pavement material characteristics, subgrade stability, construction processes, heavy vehicle loads, and increasing traffic volume. This study aims to evaluate road damage levels and determine appropriate treatment recommendations for road sections in Central Bengkulu Regency using the Provincial Kabupaten Road Management System (PKRMS) method. The research method was conducted through field surveys to collect road inventory and pavement condition data, followed by data processing and analysis using the PKRMS application. The evaluation results indicate variations in road conditions ranging from good to severely damaged, with recommended treatments including routine maintenance, periodic maintenance, and rehabilitation. The implementation of PKRMS provides data-based information that supports more effective planning and management of regional road maintenance. This study demonstrates that the application of technology-based road management systems can improve the accuracy of infrastructure maintenance priority determination.